Stop the Violence: Breaking the Cycle of Anti-Black Violence - Douglas, Kelly Brown (Interpretation, 2017)
This article examines narratives of anti-blackness and the myth of white superiority to clarify why violence against black bodies is part of American identity and to discern how that cycle of violence might be broken. Churches are vital in the process of opening white minds to the realities and consequences of American myths of anti-blackness and white supremacy. Until such a time as churches become literate in all facets of systemic racism, the cry to “stop the violence” will be meaningless.